Are regional variations in activity of dispatcher-assisted cardiopulmonary resuscitation associated with out-of-hospital cardiac arrests outcomes? A nation-wide population-based cohort study. (January 2016) - Nishi, Taiki; Kamikura, Takahisa; Funada, Akira; Myojo, Yasuhiro; Ishida, Tetsuya; Inaba, Hideo
Abstract: Aim: Dispatcher-assisted cardiopulmonary resuscitation (DA-CPR) impacts the rates of bystander CPR (BCPR) and survival after out-of-hospital cardiac arrests (OHCAs). This study aimed to elucidate whether regional variations in indexes for BCPR and emergency medical service (EMS) may be associated with OHCA outcomes. Methods: We conducted a population-based observational study involving 157, 093 bystander-witnessed, resuscitation-attempted OHCAs without physician involvement between 2007 and 2011. For each index of BCPR and EMS, we classified the 47 prefectures into the following three groups: advanced, intermediate, and developing regions. Nominal logit analysis followed by multivariable logistic regression including OHCA backgrounds was employed to examine the association between neurologically favourable 1-month survival, and regional classifications based on BCPR- and EMS-related indexes. Results: Logit analysis including all regional classifications revealed that the number of BLS training course participants per population or bystander's own performance of BCPR without DA-CPR was not associated with the survival. Multivariable logistic regression including the OHCA backgrounds known to be associated with survival (BCPR provision, arrest aetiology, initial rhythm, patient age, time intervals of witness-to-call and call-to-arrival at patient), the following regional classifications based on DA-CPR but not on EMS were associated with survival: sensitivity of DA-CPR [adjusted odds ratio (95% confidence intervals) for advanced region; those for intermediate region, with developing region as reference, 1.277 (1.131–1.441); 1.162 (1.058–1.277)]; the proportion of bystanders to follow DA-CPR [1.749 (1.554–1.967); 1.280 (1.188–1.380)]. Conclusions: Good outcomes of bystander-witnessed OHCAs correlate with regions having higher sensitivity of DA-CPR and larger proportion of bystanders to follow DA-CPR.